Sistem Pendukung Keputusan Pemilihan Vendor Pengadaan Barang Dan Jasa Pada Perumda Pasar Jaya Dengan Menggunakan Metode Analytical Hierarchy Process - Abdul Malik Yasin; ragil wijianto; Aprih Widayanto (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Bina Sarana Informatika, 2022)
Procurement of goods and service selection is one of the most important activity in a company. Vendor selection is a multi criteria problem which includes legality, financial statements, address checking, price and production capacity. For thus reason selecting the best vendor will affect a lot on desired working quality expectation. Analytical hierarchy process (AHP) can be utilized as one of effective method, by this means the value from a critieria of selection are not defined at the beginning but through priority scales formula (level of importance). This research was conducted at Perumda Pasar Jaya who will develop a partnership with PT. Damai Prima Tangguh, PT. Han awal, and PT. Rekan Sukses Sejahtera to complete a project According to the result of priority scales (level of importance) value research in vendor selection, PT Damai proma tangguh is chosen as the first by employee with 0,514 value score, the second one to be chosen is pt han awal with 0,274 value score, and the last place is pt rekan sukses sejahtera with 0,208 vakue score. The ideal vendro According to the analysis above is PT Damai Prima Tangguh. Keywords: Vendor selection, Analytical Hierarchy Process (AHP), Best vendor